'The Perfect Hostess': Mrs. Dalloway, Gift Exchange, and the End of Laissez-Faire. Issue 2 (October 2014) - Colesworthy, Rebecca
<x xml:space="preserve">Abstract</x> This paper intervenes in the longstanding debate over modernism's relationship to the market by taking the publication of Woolf's Mrs. Dalloway and Marcel Mauss's landmark essay, The Gift, in 1925 as a prompt to remap the historical and conceptual intersections between Anglo-American modernist literature, economic discourse, and twentieth-century theories of gift exchange. Drawing a crucial distinction between a modernist fascination with the gift and a modernist fascination with the primitive, I argue that Mauss uniquely conceived what John Maynard Keynes called the "end of laissez-faire" in terms of a shift in our collective thinking about gifts and exchanges. Via her sympathetic and critical characterization of Clarissa Dalloway, Woolf then figures this shift in terms of the emergence of a feminine ethos of hospitality. In furthermore establishing literature's centrality to fostering this ethos, she also anticipates, while historicizing and gendering, the structuralism of Lévi-Strauss, one of Mauss's primary heirs.